2008
DOI: 10.1073/pnas.0804286105
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4–CCR5: A couple modulating T cell functions

Abstract: Chemokines and their receptors direct leukocyte migration among blood, lymph and tissues. Evidence has recently accumulated that, besides their chemotactic functions, chemokine receptors are highly versatile players that fine tune immune responses. During human T cell activation by antigen-presenting cells, the chemokine receptors CCR5 and CXCR4 are recruited into the immunological synapse, where they deliver costimulatory signals. However, the molecular mechanisms allowing signaling versatility of chemokine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
175
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(192 citation statements)
references
References 29 publications
7
175
1
Order By: Relevance
“…In a recent study, Molon et al (20) showed that signals transduced by CCL5, via CCR5, are required for effective T cell activation. Subsequently, Contento et al (21) showed that during T cell activation by APCs, the chemokine receptors CCR5 and CXCR4 are recruited into the immunological synapse, where they deliver costimulatory signals mediated by their hetro-oligomerization. Very recently, Camargo et al (22) showed that the interaction between CCR5 and its ligands induces signals via NFAT translocation, leading to IL-2 production by CD4 + T cells, and that IL-2 production is highly related to CCR5 expression.…”
mentioning
confidence: 99%
“…In a recent study, Molon et al (20) showed that signals transduced by CCL5, via CCR5, are required for effective T cell activation. Subsequently, Contento et al (21) showed that during T cell activation by APCs, the chemokine receptors CCR5 and CXCR4 are recruited into the immunological synapse, where they deliver costimulatory signals mediated by their hetro-oligomerization. Very recently, Camargo et al (22) showed that the interaction between CCR5 and its ligands induces signals via NFAT translocation, leading to IL-2 production by CD4 + T cells, and that IL-2 production is highly related to CCR5 expression.…”
mentioning
confidence: 99%
“…This fact is the case of the two main HIV-1 coreceptors, CXCR4 and CCR5. When coexpressed on a cell and in the absence of ligands, these two receptors form heterodimers (39,40,44) that appear to modulate lymphocyte functions (40). This effect is compatible with the consensus for the G protein-coupled receptors (GPCR), which considers heteromers as entities whose function differs from that of the individual receptors (45).…”
Section: Ccr5 Expression In Cd4/cxcr4 Cells Blocks Gp120 Iiib -Inducementioning
confidence: 72%
“…(18,19,26,35,37,38). Although heterodimer stabilization is associated with specific signaling events (39)(40)(41) and with modulation of individual receptor activity (36,42,43), the functional relevance of these complexes remains unclear. This fact is the case of the two main HIV-1 coreceptors, CXCR4 and CCR5.…”
Section: Ccr5 Expression In Cd4/cxcr4 Cells Blocks Gp120 Iiib -Inducementioning
confidence: 99%
“…CXCR4 has been shown to associate with multiple chemokine receptors in various expression systems (3,(25)(26)(27)(28). ARs are also known to be able to form heteromeric receptor complexes (29)(30)(31)(32)(33)(34)(35), and recent evidence suggests that AR may also be able to form heteromeric complexes with chemokine receptors (36)(37)(38).…”
mentioning
confidence: 99%